Design and Manufacture of Orifice Tube Car Air Conditioning System Simulator with R134a Cooling Fluid - Andrizal Andrizal; Hendra Dani Saputra; Dedi Setiawan; M Yasep Setiawan (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2020)
Car air conditioning system simulator is a tool that can be used to learn the mechanism of action and the performance of the air conditioning system with certain treatments. The purpose of this research is to be able to design, make a simulator of air conditioning system type of orifice tube car with R134a cooling fluid to determine the mechanism of action, and analyze the performance of system using R134a cooling fluid. This research is a type of Research and Development (R & D), with the ADDIE model development procedure. Based on the results of research conducted, the final product is a valid and practical Car Air Conditioning System Simulator. Coefficience Of Performance (COP) value = 4.88, and has a practical value of 93 %. Simulator sistem pengkondisian udara mobil merupakan alat yang dapat digunakan untuk mempelajari mekanisme kerja dan unjuk kerja sistem pengkondisian udara dengan perlakuan tertentu. Tujuan dari penelitian ini adalah mampu merancang, membuat simulator sistem pengkondisian udara mobil jenis orifice tube dengan fluida pendingin R134a untuk mengetahui mekanisme kerja, dan menganalisa unjuk kerja sistem dengan menggunakan fluida pendingin R134a. Penelitian ini merupakan jenis Research and Development (R & D), dengan prosedur pengembangan model ADDIE. Berdasarkan hasil penelitian yang telah dilakukan, dihasilkan produk akhir berupa Simulator Sistem Pengkondisian Udara Mobil yang valid dan praktis. Nilai Cooefficience Of Performance (COP) = 4,88, dan memiliki nilai kepraktisan 93 %.